A systematic framework for the design, simulation and optimization of personalized healthcare: Making and healing blood. (4th October 2015) - Fuentes-Garí, María; Velliou, Eirini; Misener, Ruth; Pefani, Eleni; Rende, Maria; Panoskaltsis, Nicki; Mantalaris, Athanasios; Pistikopoulos, Efstratios N.
Highlights: The building blocks of a biomedical systems modeling framework are presented. Interactions between building blocks are reviewed; two system types are described. An example of a laboratory system type is described: artificial blood production. An example of a patient system type is discussed: leukemia treatment optimization. Other biomedical applications are briefly introduced as part of the framework. Abstract: We review the key building blocks of a design framework for modeling and optimizing biomedical systems under development in the Biological Systems Engineering Laboratory and the Centre for Process Systems Engineering at Imperial College. The framework features the following components: (i) in vitro environment, where model parameters can be obtained and new setups can be tested; (ii) in silico environment, including a simulation module for representing relevant physical or biological processes, and an optimization module, for calculating improved in vitro or in vivo outcomes; (iii) in vivo environment, from which organ and patient-specific parameters are collected and which can also implement personalized suggestions for improved outcomes. Two applications in the area of healthy and diseased blood are thoroughly discussed to exemplify the framework's characteristics. We discuss progress in the different areas and the way in which they are connected and finally propose a hybrid in vitro/in silico/in vivo platform.